Molecular gastronomy : exploring the science of flavor - This, Hervé (Arts and traditions of the table., 2006)
"Herve This (pronounced "Teess") is an internationally renowned chemist, a popular French television personality, a bestselling cookbook author, a longtime collaborator with the famed French chef Pierre Gagnaire, and the only person to hold a doctorate in molecular gastronomy, a cutting-edge field he pioneered. Bringing the instruments and experimental techniques of the laboratory into the kitchen, This uses recent research in the chemistry, physics, and biology of food to challenge traditional ideas about cooking and eating. What he discovers will entertain, instruct, and intrigue cooks, gourmets, and scientists alike. Molecular Gastronomy, This's first work to appear in English, is filled with practical tips, provocative suggestions, and penetrating insights. This begins by reexamining and debunking a variety of time-honored rules and dictums about cooking and presents new and improved ways of preparing a variety of dishes from quiches and quenelles to steak and hard-boiled eggs. He goes on to discuss the physiology of flavor and explores how the brain perceives tastes, how chewing affects food, and how the tongue reacts to various stimuli. Examining the molecular properties of bread, ham, foie gras, and champagne, the book analyzes what happens as they are baked, cured, cooked, and chilled. Looking to the future, Herve This imagines new cooking methods and proposes novel dishes. A chocolate mousse without eggs? A flourless chocolate cake baked in the microwave? Molecular Gastronomy explains how to make them. This also shows us how to cook perfect French fries, why a souffle rises and falls, how long to cool champagne, when to season a steak, the right way to cook pasta, how the shape of a wine glass affects the taste of wine, why chocolate turns white, and how salt modifies tastes."--Publisher's website